2019
DOI: 10.3390/sports7020034
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Anxiety, Emotional Intelligence, and Motivational Climate among Adolescent Football Players

Abstract: Background: Emotional and motivational factors are fundamental in the context of sport, as they directly relate to sports performance and anxiety. Methods: The present study aimed to analyze the relationships between motivational climate (MC), emotional intelligence (EI), and anxiety within a sample of footballers playing at a low level. The sample was composed of 282 registered football players aged between 16 and 18 years old (16.96 ± 0.77), playing in the lower tier in the province of Jaen (Spain). Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 74 publications
1
13
0
2
Order By: Relevance
“…Іграми середньої рухливості називають такі, в яких теж активно бере участь вся група, але характер рухів гравців відносно спокійний (ходьба, передача предметів) або рух виконується підгрупами. В іграх малої рухливості руху виконуються в повільному темпі, до того ж інтенсивність їх незначна [2,4].…”
Section: The Development Of Physical Qualities Using the Game Methods In The Training Process Ofunclassified
“…Іграми середньої рухливості називають такі, в яких теж активно бере участь вся група, але характер рухів гравців відносно спокійний (ходьба, передача предметів) або рух виконується підгрупами. В іграх малої рухливості руху виконуються в повільному темпі, до того ж інтенсивність їх незначна [2,4].…”
Section: The Development Of Physical Qualities Using the Game Methods In The Training Process Ofunclassified
“…Previous studies support that these mental disorders have been linked to various components of the HMIEM model. One of the recent studies reported that higher levels of anxiety were linked to an ego-oriented climate, while a task-oriented climate was related to lower levels of anxiety (Castro-Sánchez et al, 2019). The satisfaction of basic psychological needs is considered a mediator between motivational climate and motivation (Deci and Ryan, 2000).…”
Section: Motivational Processes and Mental Healthmentioning
confidence: 99%
“…Individuals can experience negative psychological states, such as anxiety, because they ineffectively interpret emotional stimuli, set inappropriate goals, implement ineffective coping strategies or fail to employ appropriate emotion regulation skills (Thomas et al 2017). For this research, anxiety is defined as "a negative psycho-emotional state that results when fear of events, which are not always identifiable, manifests as an exaggerated response where nervousness and worry predominate" (Castro-Sánchez et al 2019).…”
Section: Anxiety Caused By Agile Practicesmentioning
confidence: 99%
“…These findings are consistent with results of prior research. For example, male medical Iranian students perceive less test anxiety, if they have high EI (Ahmadpanah et al 2016) or young Spanish football players who have low scores in perceiving and regulating their emotions report higher levels of anxiety (Castro-Sánchez et al 2019). Recent research has indicated that EI can diminish the probability of anxiety (Abdollahi and Abu Talib 2015) and therefore can serve as a protective factor in the path from rumination to anxiety (Liu and Ren 2018).…”
Section: Ei As Protective Factor For Anxietymentioning
confidence: 99%